Taming the big data tidal wave : finding opportunities in huge data streams with advanced analytics - Franks, Bill (Wiley & SAS business series)
"How to approach creating and evolving a world-class advanced analytics ecosystem in today's big data environment. Written in an informal style by someone who has lived analytics in big business, Taming the Big Data Tidal Wave provides a "from the trenches" viewpoint of analytics. This book shows how big data is changing the world of analytics; what people, processes, technologies, and mindsets are necessary to succeed in analytics in this new era; what trends are developing that will change how businesses do analytics as big data alters the scale of the inputs and growing requirements change the scale of the outputs; and how to think bigger in terms of what analytics can do for a business. Looks at what big data is and why it's important. Examines some of the types of big data and how can they be used to drive new, innovative analytics. Offers the tools and technologies required to tame big data. Reveals the analytic processes and methods needed to bring about change. Discusses how your organization can set itself up for successful analytic innovation. This important book reveals how analytics has evolved in the past decades and how it will continue to evolve in the coming decades. The big data tidal wave is coming. Organizations can either ride the wave to drive analytical innovation and improve their businesses, or they can get dragged under it as it crashes on top of them. This book provides a roadmap for riding the wave successfully in terms that anyone with an interest in the topic will be able to understand"--